PENINGKATAN AKTIFITAS DAN HASIL BELAJAR DENGAN METODE PROBLEM BASIC LEARNING (PBL) PADA MATA PELAJARAN TUNE UP MOTOR BENSIN SISWA KELAS XI DI SMK INSAN CENDEKIA TURI SLEMAN TAHUN AJARAN 2015/2016 - Hermawan Budi Santoso; Subagyo Subagyo (Jurnal Taman Vokasi, 2017)
The aim of this research is to know the increase of learning activityand result using Problem Based Learning in motorbike gasoline Tune-up lesson for students in grade XI SMK Insan Cendekia Sleman. This research is a kind of action research, which in the process applying the PBL method. This research has 4 steps, which are planning, application, observation and reflection. The observation of students activity in applying PBL learning is done by going to the class directly while the learning process is still ongoing. While, the result of student learning is measured by first assessment and final assessment. The result shows that after PBL method which is given to the students there is an increase of learning activity in amount 60%, while the increase of learning result in time of observation is approximately getting 6,5 for average mark First cycle, the average mark is 6,5, while for the second cycle 6,8 and 7,3 for third cycle. These evidences show PBL method application can increase the learning activity and result using Problem Based Learning in motorbike gasoline Tune-up lesson for students in grade XI SMK Insan Cendekia Sleman